2007
DOI: 10.1503/cmaj.050258
|View full text |Cite|
|
Sign up to set email alerts
|

Septic arthritis in patients with pre-existing inflammatory arthritis

Abstract: The case: A 56-year-old woman presents to her family physician with a 7-day history of tenderness, swelling and redness of 2 metacarpophalangeal joints and 1 proximal interphalangeal joint in her right hand. She also reports pain and redness of her right knee that makes it difficult to walk. On examination, her right knee appears swollen and red. The patient has a 10-year history of rheumatoid arthritis with intermittent polyarticular flares, primarily involving her wrists, fingers (metacarpophalangeal and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…This correlates with other reports citing that the knee is affected in more than 50% of septic arthritis cases. 2,11,16 S. aureus was the most common pathogen isolated and all six isolates were detected by all three culture methods. Worldwide, S. aureus remains the most common cause of septic arthritis.…”
Section: Discussionmentioning
confidence: 91%
“…This correlates with other reports citing that the knee is affected in more than 50% of septic arthritis cases. 2,11,16 S. aureus was the most common pathogen isolated and all six isolates were detected by all three culture methods. Worldwide, S. aureus remains the most common cause of septic arthritis.…”
Section: Discussionmentioning
confidence: 91%
“…The first is Graif's [14] analysis of difference between septic and non-septic joint in naïve patients (without preexisting diagnosis of inflammatory arthritis), which provided us with the methodological background; the second is Kherani's case report [9], which focalized the importance and toughness of differentiate RA reactivation and infective complication in patients with pre-existing articular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has reported that 46% of patients with septic arthritis (SA) had a pre-existing joint disease and, of these patients, 14% had RA and 10% other inflammatory arthritis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Septic arthritis is an uncommon and potentially fatal emergency associated with significant mortality and morbidity rates, with an incidence in the general population reported to be 2 to 5 per 100,000 1 . Bacteria may spread directly from adjacent osteomyelitis or from a local soft-tissue infection, diagnostic or therapeutic procedure, or penetrating trauma 1 .…”
Section: To the Editormentioning
confidence: 99%
“…Bacteria may spread directly from adjacent osteomyelitis or from a local soft-tissue infection, diagnostic or therapeutic procedure, or penetrating trauma 1 . Usually, this condition is caused by S. aureus, which accounts for two-thirds of the cases, whereas septic arthritis caused by Klebsiella pneumoniae or Acinetobacter baumannii are rare conditions seldom reported 2,3,4,5 .…”
Section: To the Editormentioning
confidence: 99%